The OEIS mourns the passing of Jim Simons and is grateful to the Simons Foundation for its support of research in many branches of science, including the OEIS.
login
The OEIS is supported by the many generous donors to the OEIS Foundation.

 

Logo
Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A127080 Infinite square array read by antidiagonals: Q(m, 0) = 1, Q(m, 1) = 1; Q(m, 2k) = (m - 2k + 1)*Q(m+1, 2k-1) - (2k-1)*Q(m+2,2k-2), m*Q(m, 2k+1) = (m - 2k)*Q(m+1, 2k) - 2k(m+1)*Q(m+2, 2k-1). 10
1, 1, 1, 1, 1, -2, 1, 1, -1, -5, 1, 1, 0, -4, 12, 1, 1, 1, -3, 3, 43, 1, 1, 2, -2, -4, 28, -120, 1, 1, 3, -1, -9, 15, -15, -531, 1, 1, 4, 0, -12, 4, 48, -288, 1680, 1, 1, 5, 1, -13, -5, 75, -105, 105, 8601, 1, 1, 6, 2, -12, -12, 72, 24, -624, 3984, -30240, 1, 1, 7, 3, -9, -17, 45, 105, -735, 945, -945, -172965 (list; table; graph; refs; listen; history; text; internal format)
OFFSET
0,6
COMMENTS
Comment from N. J. A. Sloane, Jan 29 2020: (Start)
It looks like there was a missing 2 in the definition, which I have now corrected. The old definition was:
(Wrong!) Infinite square array read by antidiagonals: Q(m, 0) = 1, Q(m, 1) = 1; Q(m, 2k) = (m - 2k + 1)*Q(m+1, 2k-1) - (2k-1)*Q(m+2, k-2), m*Q(m, 2k+1) = (m - 2k)*Q(m+1, 2k) - 2k(m+1)*Q(m+2, 2k-1). (Wrong!) (End)
REFERENCES
V. van der Noort and N. J. A. Sloane, Paper in preparation, 2007.
LINKS
FORMULA
E.g.f.: Sum_{k >= 0} Q(m,2k) x^k/k! = (1+4x)^((m-1)/2)/(1+2x)^(m/2), Sum_{k >= 0} Q(m,2k+1) x^k/k! = (1+4x)^((m-2)/2)/(1+2x)^((m+1)/2).
EXAMPLE
Array begins:
1, 1, 1, 1, 1, 1, 1, 1, 1, 1, ... (A000012)
1, 1, 1, 1, 1, 1, 1, 1, 1, 1, ... (A000012)
-2, -1, 0, 1, 2, 3, 4, 5, 6, 7, ... (A023444)
-5, -4, -3, -2, -1, 0, 1, 2, 3, 4, ... (A023447)
12, 3, -4, -9, -12, -13, -12, -9, -4, 3, ... (A127146)
43, 28, 15, 4, -5, -12, -17, -20, -21, -20, ... (A127147)
-120, -15, 48, 75, 72, 45, 0, -57, -120, -183, ... (A127148)
-531, -288, -105, 24, 105, 144, 147, 120, 69, 0, ...
1680, 105, -624, -735, -432, 105, 720, 1281, 1680, 1833, ...
MAPLE
f:= proc(k) option remember;
if `mod`(k, 2)=0 then k!/(k/2)!
else 2^(k-1)*((k-1)/2)!*add(binomial(2*j, j)/8^j, j=0..((k-1)/2))
fi; end;
Q:= proc(n, k) option remember;
if n=0 then (-1)^binomial(k, 2)*f(k)
elif k<2 then 1
elif `mod`(k, 2)=0 then (n-k+1)*Q(n+1, k-1) - (k-1)*Q(n+2, k-2)
else ( (n-k+1)*Q(n+1, k-1) - (k-1)*(n+1)*Q(n+2, k-2) )/n
fi; end;
seq(seq(Q(n-k, k), k=0..n), n=0..12); # G. C. Greubel, Jan 30 2020
MATHEMATICA
Q[0, k_]:= Q[0, k]= (-1)^Binomial[k, 2]*If[EvenQ[k], k!/(k/2)!, 2^(k-1)*((k-1)/2)!* Sum[Binomial[2*j, j]/8^j, {j, 0, (k-1)/2}] ];
Q[n_, k_]:= Q[n, k]= If[k<2, 1, If[EvenQ[k], (n-k+1)*Q[n+1, k-1] - (k-1)*Q[n+2, k-2], ((n -k+1)*Q[n+1, k-1] - (k-1)*(n+1)*Q[n+2, k-2])/n]];
Table[Q[n-k, k], {n, 0, 12}, {k, 0, n}]//Flatten (* G. C. Greubel, Jan 30 2020 *)
PROG
(Sage)
@CachedFunction
def f(k):
if (mod(k, 2)==0): return factorial(k)/factorial(k/2)
else: return 2^(k-1)*factorial((k-1)/2)*sum(binomial(2*j, j)/8^j for j in (0..(k-1)/2))
def Q(n, k):
if (n==0): return (-1)^binomial(k, 2)*f(k)
elif (k<2): return 1
elif (mod(k, 2)==0): return (n-k+1)*Q(n+1, k-1) - (k-1)*Q(n+2, k-2)
else: return ( (n-k+1)*Q(n+1, k-1) - (k-1)*(n+1)*Q(n+2, k-2) )/n
[[Q(n-k, k) for k in (0..n)] for n in (0..12)] # G. C. Greubel, Jan 30 2020
CROSSREFS
See A105937 for another version.
Columns give A127137, A127138, A127144, A127145;
Rows give A127146, A127147, A127148.
Sequence in context: A330942 A141471 A331572 * A216645 A216635 A213945
KEYWORD
sign,tabl
AUTHOR
N. J. A. Sloane, Mar 24 2007
EXTENSIONS
More terms added by G. C. Greubel, Jan 30 2020
STATUS
approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified May 19 09:42 EDT 2024. Contains 372683 sequences. (Running on oeis4.)